OPTIMIZING HYBRID CLOUD ARCHITECTURES: A COMPREHENSIVE STUDY OF PERFORMANCE ENGINEERING BEST PRACTICES - Anshul Sharma (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
Hybrid cloud architectures have emerged as a pivotal solution for organizations seeking to balance the flexibility of public clouds with the control of on-premises infrastructure. However, these complex environments present unique challenges in maintaining optimal performance across diverse systems. This article examines the critical aspects of performance engineering in hybrid cloud environments, offering a comprehensive analysis of best practices and real-world implementations. We explore key strategies for optimizing workload distribution, minimizing latency, managing resources effectively, and implementing robust monitoring and observability practices. Through a series of case studies, we demonstrate the practical application of these strategies, highlighting their impact on performance metrics and overall system efficiency. Our findings underscore the importance of a holistic approach to hybrid cloud performance engineering, one that addresses the intricate interplay between on-premises and cloud resources while maintaining security and compliance. As hybrid cloud adoption continues to accelerate, the insights and methodologies presented in this article provide a valuable framework for IT professionals and organizations striving to maximize the benefits of their hybrid infrastructures while mitigating performance-related challenges